Progressão continuada no bloco pedagógico: desafios para a gestão escolar em uma escola pública da rede municipal de Santa Maria-RS - Rodrigues, Kátia Rezende (2018)
This Professional Master's research falls under the Public Policies and Elementary Education Management line of the Postgraduate Program in Public Policies and Educational Management. It refers to the discussion on the continuous progression of the initial years of elementary education. The objective of this research was to analyse the demands and challenges of school management concerning the regulation of continuous progression in the pedagogical field of the initial years of elementary education from a school of the Santa Maria’s municipal network. The methodological processes are based on the qualitative approach (FLICK, 2009) and the adopted methodology is study case (GIL, 2009). The documentary analysis (GIL, 2008) was based on the national and the municipal legislation, as well as the official school documents. The survey of data was anchored in non-standardized interviews (LAKATOS & MARCONI, 2003) with managers and teachers of the target-school and participant observation (GIL, 2008). For data analysis, it was considered data triangulation (FLICK, 2009) and content analysis (BARDIN, 2009). The theoretical reference was organized from Akkari (2011), Brandalise (2010), Dourado (2007), Ferreira (2009), Freire (1997), Freitas (2003, 2012) Haydt (2008), Libâneo (2009), Lück (2009), Luckesi (2005), Oliveira (2002), Paro (2003), Perrenoud (1999), Sander (2009) and Vieira (2009). As a final product of this Master's Degree research, the School Management Plan of the Pedagogical Field was elaborated in the strategic planning bias. The studies point that continuous progression represents the possibility to assist the interpretation of continuous progression in the pedagogical field. The comprehension of the proposal’s dynamics of public policy seen as a way to (re)organize time and space and to attenuate exclusion acts (school drop-out, failure) represents an instrument of resistance and empowerment to claim adequate conditions for the functioning, which promotes the success and permanence of the students in the school. Therefore, the school management based on participatory and democratic action leads to the success of the pedagogical act.